MPLEMENTASI FUNGSI POKOK MANAGEMEN HUMAS PADA YAYASAN PENDIDIKAN - Fahrudin, Budi Arif; Halwati, Umi (Jurnal Isema : Islamic Educational Management, 2023)
The MI Ma'arif NU Banjarsari Education Foundation is an educational institution committed to providing quality educational services for students and the community. In this effort, educational institutions need good public relations management to build a positive image, expand cooperation networks, and increase community participation in educational activities. In this article, we discuss the main functions of education public relations management according to experts and the importance of public relations management in the administration of education. We also review the implementation of public relations management carried out by the MI Ma'arif NU Banjarsari Education Foundation, from planning, implementation, to evaluation. The evaluation includes evaluating customer satisfaction, evaluating employee performance, evaluating learning programs, and evaluating social activities. By conducting periodic evaluations, the MI Ma'arif NU Banjarsari Education Foundation can correct existing deficiencies and improve the quality of education services provided to students and the community.